Perancangan Lembar Evaluasi Komunikasi Antar Internal Departemen Demi Tercapainya Umpan Balik Di PT. XYZ - Cinthia Gunawan; Jani Rahardjo (Jurnal Titra, 2015)
Evaluation communicaton questionnaire has an important role in improving the internal department working performance because it can dig criticisms, suggestions and constructive feedback to each department. PT. XYZ is not currently using any evaluation questionnaire to dig internal department feedback. The purpose of this research is to design communication evaluation questionnaire to achieve feedback from another department. The technique that used in this study is semi-structured interview to the respondents who selected using judgment sampling method. Analysis techniques and data processing done with the existing coding assistance in Microsoft Excel to generate descriptive data in the form of feedback between departments. Feedback for the department is divided into two types, namely strength and opportunity for improvement point. Strength point is the strength of a department that must be maintained and enhanced, while opportunity for improvement point points should be used as a reflection to improve the department for the better future.